Injuries and illnesses among competitive Norwegian rhythmic gymnasts during preseason: a prospective cohort study of prevalence, incidence and risk factors - Gram, M. C. D.; Clarsen, B.; Bo, K. (British Journal of Sports Medicine, 2021)
Objectives: Rhythmic gymnastics is an Olympic sport that demands high training volume from early age. We investigated the extent of, and risk factors for, injuries among competitive Norwegian rhythmic gymnasts.